Respuesta :
3a^5 - (-a^5) = 3a^5 + a^5 = 4a^5
6a^7 - 2a^7 = 4a^7
-3a^5 - (-2a^5) = -3a^5 + 2a^5 = -a^5
7a^7 - 8a^7 = -a^7
6a^7 - 2a^7 = 4a^7
-3a^5 - (-2a^5) = -3a^5 + 2a^5 = -a^5
7a^7 - 8a^7 = -a^7
Answer: The simplified of the given expression shown below.
Step-by-step explanation:
Since, First expression, [tex]3a^5-(- a^5)[/tex]
We can write [tex]3a^5-(- a^5)[/tex]=[tex]3a^5+a^5[/tex] = [tex]4a^5[/tex]
Second expression, [tex]6a^7 - 2a^7[/tex]
⇒[tex]6a^7 - 2a^7= 4a^7[/tex]
Third expression [tex]-3a^5 - (-2a^5)[/tex]
⇒ [tex]-3a^5 - (-2a^5)[/tex] = [tex]-3a^5 + 2a^5[/tex] = [tex]-a^5[/tex]
Fourth expression, [tex]7a^7 - 8a^7[/tex]
⇒ [tex]7a^7 - 8a^7 = -a^7[/tex]